Binding Site Effect in Metal‐Organic Frameworks for Property Regulation of Metal Nanoparticles. Issue 5 (16th February 2021) - Wu, Peng; Shen, Yu; Li, Hongfeng; Shi, Wenxiong; Zhang, Lulu; Pan, Ting; Pei, Wenbo; Zhang, Weina; Huo, Fengwei
Abstract : Metal nanoparticles (MNPs) supported on metal–organic frameworks (MOFs) have exhibited excellent performance in various catalytic reactions. As a class of crystal catalysts, the roles played by MOFs different positions in regulating the MNPs properties are distinct. It is therefore meaningful to clarify the influence of different positions of MOFs on MNPs to help reveal the structure–activity relationship. However, the random dispersion of MNPs in the MOFs matrixes is usually an obstacle existing in the traditional preparation methods. Herein, a facile strategy is developed to precisely control the MNPs growth behavior on the target binding sites of MOFs. The MNPs on edges of MOFs show significantly improved hydrogen evolution reaction performance in comparison to those on the planes of MOFs, mainly because the electronic structure of MNPs is regulated by special interface originating from MNPs growth on the edges of MOFs, which provides high density of unsaturated copper ions. The effect of different binding sites of MOFs on MNPs properties is clarified, which is highly desired for fine‐tuning the structures and properties of the MOF composites. Abstract : A series of metal nanoparticles (MNPs)/metal–organic frameworks (MOFs) catalysts with well‐defined binding sites are obtained by fine controlling the MNPs growth behavior on the target binding sites of MOFs. Interestingly, the MNPs loading on different binding sites of MOFs can regulate the electronic structure of MNPs for improving hydrogen evolution reaction (HER) performance.